Embodied Pedagogies: the construction of feminist knowledge in agroecological production in southeastern Buenos Aires, Argentina (Palimpsesto, 2026)
This research explores the intersection of feminist pedagogies, the category of body-territory, and agroecological practices in southeastern Buenos Aires, Argentina. By analyzing the university outreach project “Cocinas Soberanas” (Sovereign Kitchens) from the National University of Mar del Plata, the study investigates the knowledge-building processes emerging from the encounter between academia and the territory. A territorialized qualitative methodology with a narrative-interpretative approach was employed, adopting a critical, decolonial, and gender perspective. The findings demonstrate that the leading role of women producers transforms the educational event, shifting traditional outreach toward a Embodied Pedagogies. This praxis revalues sensory, relational, and culinary knowledges as political and emancipatory, leaving a tangible “trace” that tensions the dichotomy between body and territory. The study concludes that agroecology, when lived through presence and affect, constitutes a tool of resistance against cisheteronormativity and extractivism.
Keywords: Feminist pedagogy; Feminist knowledge; Body-territory; Agroecology; Food sovereignty